KUALITAS PELAYANAN PUBLIK TERHADAP KEPUASAN SERTA KEPERCAYAAN MASYARAKAT PADA KEPOLISIAN SEKTOR (POLSEK) BENGALON - Hidayati, Tetra (Journal of Innovation in Business and Economics, 2014)
The purpose of the study is to determine the direct and indirect impact of real evidence, test power, responsiveness, competence, courtesy, credibility and easiness of accessing toward the satisfaction and trust of Police Sector (Polsek) Bengalon. To answer the problem, the study uses path analysis. The results of this study found that responsiveness, competency, courtesy and credibility were directly giving a significant impact to public satisfaction; whereas real evidence, test power and easiness of accessing were directly not giving significant impact to public trust. The variable of responsiveness and credibility were directly giving significant effect toward public trust; meanwhile, the real evidence, test power, competence, courtesy, and easiness of accessing were directly giving significant impact toward public trust. The public was directly giving no significant impact on trust of satisfaction.  The real evidence was indirectly giving negative impact on the trust through satisfaction; meanwhile, test power, responsiveness, competence, courtesy, credibility and easiness of accessing were indirectly giving positive impact on public trust through satisfaction